Current Situation and Trend of Electric Vehicle Battery Business - Take CATL as an example - Liu, Chang; Bi, Chuanchen (Technium Social Sciences Journal, 2022)
New energy vehicles are one of the most important strategic emerging industries in China. Lithium battery is the universal choice of energy supply for new energy vehicles at present, which has the advantage of security and stability compared with other new energy sources. China has a complete lithium battery industry chain from lithium mining to battery manufacturing. The CATL is one of the large enterprises of this chain. However, with the rise of domestic competitors, foreign enterprises such as LG Chem have entered the Chinese market strongly. The intensification of market competition and the possible adjustment of national policies make the development of CATL facing many challenges. As early as before the COVID-19, the profits of CATL had declined, and the research on the strategic development of CATL has important practical significance. This paper analyzes the advantages and disadvantages, opportunities and threats faced by the power battery business of CATL through the SWOT analysis model. Based on the analysis of the development strategic direction corresponding to the combination of the four elements of the internal and external environment in the model, it is concluded that under the background of the emerging new energy vehicle industry and the gradual improvement of the market, CATL should seek diversified development strategic direction (ST strategy).